REGE (Recycle Vegetable Waste): Pemberdayaan Limbah Sayur Menjadi Pupuk Organik Padat dan Cair Ramah Lingkungan di Pasar Koto Baru - Muhammad Rizki Pratama; Hasnah Wita; Feby Handayani; Rudi Kurniawan; Joni Saputra; Kit Nada; Muchlisinalahuddin Muchlisinalahuddin; Helga Yermadona; Femi Earnestly (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Compost has some advantages, improving soil physical properties, chemical properties, and biological properties. It happens because its characteristics contain nutrients in varying types and amounts depending on the original material, provide nutrients slowly (slow release) and in limited quantities, and have the main function of improving soil fertility and health. The pile of organic waste from the Koto Baru market directly impacts the environment to their community. This Community Service Program aims to increase the knowledge and skills of target communities about processing vegetable waste from the Koto Baru market into the solid and liquid-friendly environment of organic fertilizers. The target people of this activity were PKK Jorong Subarang Nagari Koto Baru women in particular and people who wrote Jorong Subarang Nagari Koto Baru. The methods used in this service were socialization of the processing of vegetable waste from the Koto Baru market into the solid and liquid-solid and liquid friendly environment of organic fertilizers, distribution of practical manuals for assembling tools for making solid and liquid organic fertilizer from vegetable waste, distributing initial questionnaires to online socialization. This activity had positive impacts on these PKK women, including providing knowledge of PKK women about the use of organic vegetable waste from the Koto Baru market to become a POP friendly environment and POC, the dissemination of information on the use of vegetable waste from the Koto Baru market became a solid and liquid friendly environmental of organic fertilizer in Jorong Subarang Nagari Koto Baru, Tanah Datar Regency.